Development of Jataka Pop-Up Book As Instructional Media for Sunday School Buddhist Students at Culla Sekha Level - pradana, Joko Adi; Utomo, Budi; Muslianty, Devy (Jurnal Paedagogy, 2023)
This research aims to develop a Pop-up Book about Jataka stories as a learning material for Culla Sekha level students at the Buddhist Sunday School. The research method used was development research with the 4D model, which includes Define, Design, Develop, and Disseminate phases. This research was carried out at the Buddhist Sunday School in the Gladagsari sub-district, involving teachers and students. The data collection technique distributed questionnaires for groups of students and two expert respondents: a media expert and a Jataka material expert. The data analysis technique used descriptive statistics in the form of percentage analysis. The research results showed that the development of the Pop-up Book media obtained an average percentage of 93% in the "very good" category according to the media expert, 84% in the "good" category according to the material expert, and 92.7% in the "very good" category based on student responses. From these research findings, the development of the Jataka Pop-up Book has excellent quality. This Pop-up Book could effectively support the learning process, as it received positive feedback from the media expert, material expert, and students.